Health-care-associated infection in a pediatric intensive care unit - Diwakar, Kumar; Kumar, Ratan; Mishra, Sudhir; Gupta, Minakshi (Indian Journal of Child Health, 2019)
Introduction: Health-care-associated infection (HAI) is a major cause of concern in pediatric intensive care units (PICUs) all over the world and represents an important cause of mortality and financial burden for health-care systems. Objective: The objective of this study was to describe the epidemiologic profile of children with HAI. Methods: This was a prospective surveillance study conducted in a pediatric intensive care unit of a tertiary care hospital, India. Children, admitted to PICU between December 1, 2015, and November 30, 2016, were monitored for the development of bloodstream infection (BSI), ventilator-associated pneumonia, andurinary tract infection. Results: A total of 430 patients were admitted during the study period. Of 250 eligible patients, 15 children(6%) developed 19 episodes of HAI with patient prevalence of six infections per 100 patients. Only Gram-negative bacteria were identified, Klebsiella pneumoniae was the most common organism (68.42%). Bloodstream was the most common site of HAI (n=11, 58%) followed by respiratory tract (n=6, 32%) and urinary tract (n=2, 10%). In a univariate analysis, survivors of cardiac arrest or trauma, malnourished children had an increased risk of acquiring HAI. The presence of lymphopenia (?1000/mm3), hypercarbia (Pco2 >65 mmHg), sodium imbalance (150 meq/L), organ dysfunctions, and length of stay before acquiring infection was all associated with an increased risk of developing HAI (p